1979
DOI: 10.1021/ja00503a029
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry and mechanism for the palladium(II)-catalyzed oxidation of ethene in water (the Wacker process)

Abstract: Palladium(II)-catalyzed oxidation of specifically deuterated ethenes in water in the presence of cupric chloride and chloride ion has been studied. Stereospecific formation of threo-1,2-dideuterio-2-chloroethanol (threo-3) from (£)-1,2-dideuterioethene ((£')-2) indicates that the hydroxypalladation step in the Wacker oxidation is a trans process. Generation of an eryiAro-jS-hydroxyethylpalladium complex (6) from eryzAro-^-hydroxyethylmercuric chloride (5) in the presence of CuCl2-LiCl also results in the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
122
0
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 302 publications
(130 citation statements)
references
References 6 publications
5
122
0
3
Order By: Relevance
“…[28] However, experiments conducted by Akermark, Stille, Bäckvall, and co-workers demonstrated that palladium ligated with substituted or deuterium-labeled alkenes formed products by anti oxypalladation. [29][30][31][32] For example, the addition of CO to the combination of bis[(cis-[D 2 ]ethylene)PdCl 2 ] and H 2 O in a buffered solution of CuCl 2 and NaOAc led to the formation of lactone products, and the configuration of the carbon atoms in the lactone indicated that an anti addition of the oxygen atom and palladium to the ethylene had occurred. [30] In fact, Bäckvall, Siegbahn, and coworkers stated that a hydroxymetal olefin complex is too unreactive to undergo cis migration of an OH ligand to a bound alkene.…”
Section: Catalytic Reactions Involving Alkene Insertion Into Mào Bondsmentioning
confidence: 99%
“…[28] However, experiments conducted by Akermark, Stille, Bäckvall, and co-workers demonstrated that palladium ligated with substituted or deuterium-labeled alkenes formed products by anti oxypalladation. [29][30][31][32] For example, the addition of CO to the combination of bis[(cis-[D 2 ]ethylene)PdCl 2 ] and H 2 O in a buffered solution of CuCl 2 and NaOAc led to the formation of lactone products, and the configuration of the carbon atoms in the lactone indicated that an anti addition of the oxygen atom and palladium to the ethylene had occurred. [30] In fact, Bäckvall, Siegbahn, and coworkers stated that a hydroxymetal olefin complex is too unreactive to undergo cis migration of an OH ligand to a bound alkene.…”
Section: Catalytic Reactions Involving Alkene Insertion Into Mào Bondsmentioning
confidence: 99%
“…15 Some authors, however, suggested that these stereochemical studies supporting the anti pathway might not be relevant to the mechanism of the Wacker process because the reaction conditions are not those of the common Wacker process (low [Cl [PdCl 3 (pyridine) -] in aqueous solution (in the presence and absence of CuCl 2 ) showed that the rate law was the same at low [Cl -] as for the regular catalyst used in the Wacker process; the reaction, however, was significantly slower. 17 The product distribution observed was consistent with a mechanism involving 5 an anti addition at high [Cl -] and a syn addition at low [Cl -].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, such studies should assess whether nucleophilic attack is an equilibrium process. Although quinone was used as reoxidant for Pd, the rate law observed was the same as in the Wacker process 15 (eq. 4).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations